Unique catalytic properties of a butoxy chain-containing ruthenated porphyrin towards oxidation of uric acid and reduction of dioxygen for visible light-enhanced fuel cells. (10th September 2016) - Liu, Junchen; Wang, Yi; Deng, Qiang; Zhu, Licai; Chao, Hui; Li, Hong
Graphical abstract: Highlights: Ru(II)PTPP/CdS shows two Ru(II)-based oxidation peaks at 0.296 V and 0.830 V. Photoelectrocatalytic oxidation of UA exhibits good linear responses. The butoxy chain endows Ru(II)PTPP with multifunctional catalytic properties. Ru(II)PTPP on CF electrode can remarkably promote the reduction of oxygen. The assembled cell has I SC of 0.136 mA cm −2 and P max of 31.50 μW cm −2 . Abstract: This paper reports the photoelectrocatalytic activities of a ruthenated porphyrin [Ru(phen)2 (IP-C4 O-TPP)] 2+ (denoted as Ru(II)PTPP, phen = 1, 10-phenanthroline, IP = imidazo[4, 5- f ][1, 10]phenanthroline and TPP = 5, 10, 15, 20-tetraphenylporphyrin) containing a covalently-linked butoxy chain (-C4 O-) between IP and TPP moieties by means of various electrochemical techniques in combination with absorption spectroscopy and scanning electronic microscopy. Ru(II)PTPP is assembled on the surface of CdS nanoparticles, showing two Ru(II)-based peaks at 0.296 V and 0.830 V, where uric acid (UA) can be photoelectrocatalytically oxidized in a linear range of 0.01-10.0 mmol L −1 . The −C4 O- chain endows the Ru(II)PTPP/carbon felt (CF) electrode with favorable dioxygen (O2 ) binding sites to achieve a couple of new redox peaks at −0.213 V, where O2 involves electrocatalytic reduction reactions. While employing 5.0 mmol L −1 UA as fuel, and 60 mL min −1 O2 as oxidant, the proposed photoelectrochemical fuel cell shows open-circuit photovoltage of 0.656 V, short-circuit photocurrent density of 0.136 mA cm −2, and maximum power density of 31.50 μW cm −2 at 0.497 V under visible-light illumination of 0.18 mW cm −2 . The present study provides an interesting platform for the utilization of renewable energy sources.